Secular Theology? Antipodean Annotations - Grimshaw, Mike 1967- (2010)
A response from an antipodean perspective to the discussion on Secular theology conducted in the CSSR Bulletin April-September 2008. The article enages with the essays on secular theology, suggests the use of para- as a prefeix rather than post- for 'post-secular' and further suggests rethinking secular theology as a series of approaches in common with critical theory. It argues for a rethinking of secular theology as a series of approaches perhaps best conducted from the social sciences.
Keywords: Critical Theory; Secular Theology